STUDI DAMPAK MASUKNYA PT. DONGGI SENORO TERHADAP PENGELUARAN KONSUMSI RUMAH TANGGA DI KECAMATAN KINTOM KABUPATEN BANGGAI - Satang, Saprin Satang (Katalogis, 2015)
This study aimed to describe the impact of the entry of PT.Donggi-Senoro LNG (DSLNG) against the living conditions of the people in the District Kintom, and analyze the influence of income, education, occupation, and number of dependents of the consumption expenditure of the poor in the District Kintom.Type of survey research, using cross section data obtained from interviews directly to the respondents using a questionnaire regarding the characteristics of the respondents.Sampling purposive sampling technique, so as to obtain the key respondents by 99 people.This study uses qualitative analysis to decipher the impact of the entry of PT.Donggi-Senoro LNG (DSLNG) on the living conditions of society, using multiple linear regression to see the influence of income, education, occupation, and number of dependents of the consumption expenditure of the poor in the District Kintom. Tools used to manage the data of this study was SPSS-21.Results of the study found that the impact of the entry of PT.Donggi - Senoro LNG (DSLNG), against the District Kintom people's living conditions, among others: the increase in income, employment, improving public education, and disruption of social processes.Medium for statistical analysis of the consumption of poor households shows that the coefficient of determination (R) for, 757 which means that the variation of independent variables RTM District of Kintom consumption by 75.70%.Significance Simultaneous detection (Test Statistic F) and obtained the F-table at 2.47 (Î±: 5%, and df: 99-4 = 95) while the statistical F/F-count of 31.462 and F-statistic probability value 0,000.Medium for Detection of Individual Parameter Significance (Test Statistics T) obtained t-table value of 1.661.Based on the t-table value with the assumption of the t-statistics/t count003e t-table, the independent variables were significant to the variable household consumption is variable income (t-test = 5.328), and the number of dependents (t-test = 3824).Based on the research results suggested to PT.DSLNG to be more structured in implementing CSR, and for the Government of the District Kintom need to create policies that can improve / increase the income of poor households are not able to meet the basic consumption needs in order to prosper and be able to meet their basic needs.And also suggested that the Government of the District Kintom more proactive in controlling the implementation of CSR given PT.DSLNG to society, so that more people benefit from CSR.